Mid- to late-Holocene sea-level evolution of the northeastern Aegean sea. (October 2021) - Seeliger, Martin; Pint, Anna; Frenzel, Peter; Marriner, Nick; Spada, Giorgio; Vacchi, Matteo; Başaran, Sait; Dan, Anca; Seeger, Friederike; Seeger, Katharina; Schmidts, Thomas; Brückner, Helmut
We combined biostratigraphical analyses, archaeological surveys, and Glacial Isostatic Adjustment (GIA) models to provide new insights into the relative sea-level evolution in the northeastern Aegean Sea (eastern Mediterranean). In this area, characterized by a very complex tectonic pattern, we produced a new typology of sea-level index point, based on the foraminiferal associations found in transgressive marine facies. Our results agree with the sea-level history previously produced in this region, therefore confirming the validity of this new type of index point. The expanded dataset presented in this paper further demonstrates a continuous Holocene RSL rise in this portion of the Aegean Sea. Comparing the new RSL record with the available geophysical predictions of sea-level evolution indicates that the crustal subsidence of the Samothraki Plateau and the North Aegean Trough played a major role in controlling millennial-scale sea-level evolution in the area. This major subsidence rate needs to be taken into account in the preparation of local future scenarios of sea-level rise in the coming decades.